Speech text of 1st international conference on food, nutrition & health (ICFNH) 2023 / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
A very warm welcome to all participants and esteemed guests from near and far to the 1st International Conference on Food, Nutrition & Health (ICFNH) 2023.